2021
DOI: 10.1177/20563051211009013
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation Concerns and Online News Participation among internet Users in India

Abstract: The rise of misinformation often circulated in various social media platforms has not only raised concerns among the policymakers and civil society groups, but also among citizens. Drawing upon a cross-sectional survey ( n = 1,013) among English-language internet users in India, this paper tries to identify factors that affect concerns for online misinformation among citizens and how online news participation is affected by the rise of misinformation. After controlling for gender, age, education and income, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…While a recent study conducted in India ( Neyazi, Kalogeropoulos, & Nielsen, 2021 ) found no correlation between misinformation concerns and online news sharing, concern about “fake news” and inaccurate information on social networks has been very high in the U.S. ( Newman et al, 2019 ). Given the incipient level of the crisis, and as increased doubts and debates on facts regarding a risk event may heighten public uncertainty and may influence the credibility of information sources ( Kasperson et al, 1988 ), the present study argues that misinformation concerns may alter the degree to which online interpersonal discussions and trusted sources affect risk amplification and information sharing behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…While a recent study conducted in India ( Neyazi, Kalogeropoulos, & Nielsen, 2021 ) found no correlation between misinformation concerns and online news sharing, concern about “fake news” and inaccurate information on social networks has been very high in the U.S. ( Newman et al, 2019 ). Given the incipient level of the crisis, and as increased doubts and debates on facts regarding a risk event may heighten public uncertainty and may influence the credibility of information sources ( Kasperson et al, 1988 ), the present study argues that misinformation concerns may alter the degree to which online interpersonal discussions and trusted sources affect risk amplification and information sharing behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…These contradictions can be caused by the method and level of use of social networks and the level of emotional-social dependence due to cultural-social limitations. The rise in these contradictions is alarming not only for policymakers and civil community groups but also for the citizens [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some personality traits characterise users who share FNI: agreeableness (Buchanan and Benson, 2019) or conscientiousness (Buchanan, 2021), higher extraversion and neuroticism (Buchanan, 2020), altruism (Apuke and Omar, 2021a, c;Balakrishnan et al, 2021) or overconfidence (Lyons et al, 2021) and religious beliefs (Islam et al, 2020). Political beliefs are highly related to users' sharing behaviours (Lobato et al, 2020;McPhetres et al, 2021;Neyazi et al, 2021;Osmundsen et al, 2021;Tandoc et al, 2021). Individuals with a high cognitive ability are less trustful of FNI (Tandoc et al, 2021), including deepfakes (Ahmed, 2021a, c).…”
Section: Input Of Fnimentioning
confidence: 99%
“…Anxiety (Freiling et al, 2021), negative emotions (Wang et al, 2020) and death-related thoughts (Lim et al, 2021) are driving factors in users' willingness to share FNI. Media use habits are relevant to sharing behaviours on Facebook and Twitter (Neyazi et al, 2021). Users with decreased news consumption, high Internet use (Bringula et al, 2021) and high trust in the news on the internet (Filkukova et al, 2021) easily trust and spread FNI.…”
Section: Input Of Fnimentioning
confidence: 99%
See 1 more Smart Citation